2013
DOI: 10.1007/s11698-012-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Trade policy and wage gradients: evidence from a protectionist turn

Abstract: Abstract:In the spirit of Hanson (1997), we analyze the existence of regional nominal wage gradients in Spain during the interwar period (1914)(1915)(1916)(1917)(1918)(1919)(1920)(1921)(1922)(1923)(1924)(1925)(1926)(1927)(1928)(1929)(1930) and their transformation following an important change in trade policy. However, our case study analyzes the effects of the substitution of an open economy by a closed one -exactly the reverse of the process studied by Hanson. We find strong evidence of the existence of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…As protectionism was consolidated, the domestic market potential became more relevant than foreign markets as a driver of regional per capita growth rates. This result confirms the evidence obtained in previous analyses of the industrial sector in Spain during the interwar years (Tirado et al, 2013).…”
Section: -Empirical Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…As protectionism was consolidated, the domestic market potential became more relevant than foreign markets as a driver of regional per capita growth rates. This result confirms the evidence obtained in previous analyses of the industrial sector in Spain during the interwar years (Tirado et al, 2013).…”
Section: -Empirical Analysissupporting
confidence: 92%
“…Firstly, following the influential work by Hanson (1998Hanson ( , 2005), based in turn on the Krugman wage equation, the existence of a spatial structure in industrial nominal wages in the 1920s in Spain has been examined in Tirado et al (2013).…”
Section: Figure 1 Openness Rates (%) Spain 1850-1935mentioning
confidence: 99%
“…On the other hand, exploring the evolution of the 100 largest cities during the 20 th century, Lanaspa et al (2003) find that a convergent pattern of growth dominated between 1900 and 1970 and divergence followed thereafter. While this study is just concerned with 18 Other studies have shown the relevance of agglomeration economies in the industrial sector during the early stages of economic growth in Spain (Tirado et al, 2002;Martinez-Galarraga, 2012); examined and verified the existence of the wage equation in industrial wages (Paluzie et al, 2009a;Tirado et al, 2013); and proved the direct relationship between internal migration decisions and market access in the 20 th century (Paluzie et al, 2009b).…”
Section: Returnsmentioning
confidence: 81%
“…Crafts and Venables (2003) provided early evidence consistent with that here, but do not estimate any particular model. Tirado, Pons, Paluzie, and Martínez Galarraga (2013) find that market potential helps explain the regional wage gradient in Spain between 1914 and 1930. Donaldson (forthcoming) provides strong support for the idea that market potential was positively related to real incomes of regions in India in the 19th century.…”
Section: Introductionmentioning
confidence: 80%